Efficacy of Ma'aljobon Aftimouni (Cuscuta Reflexa and whey) on HbA1c and blood glucose levels in patients with Type 2 Diabetes: A randomized triple-blind clinical trial - Fatemeh Mehrabi; Ali Safdari; Azam Moslemi; Mehdi Salehi; Ali Agharazi; Mohammad Reza Rezvanfar (Contemporary Clinical Trials Communications, 2025)
Introduction and objective: Type 2 Diabetes is a common and chronic metabolic disease. Complementary and alternative medicine can provide a suitable option for demands for new treatments. Therefore, the present study aimed to investigate the effect of Persian medicine on the glycemic status of patients with Type 2 Diabetes. Method: This randomized, controlled, and triple-blind trial study was conducted from November 2021 to August 2022 on 102 diabetic patients referred to the diabetes clinic in Iran. In this regard, patients with inclusion criteria were randomly divided into three groups Ma'aljobon with Aftimoun (n = 34), Ma'aljobon without Aftimoon (n = 34), and the control group (n = 34). The control group received a placebo of medicinal salt, light calcium carbonate, lactose, and carboxymethyl cellulose. In contrast, the treatment groups received 25 g of drug powder (in 250 cc of lukewarm water) on an empty stomach for 8 consecutive weeks. Patients' fasting blood sugar (FBS) levels and HbA1c were measured at the beginning and end of the intervention. Data were analyzed using SPSS 23, employing paired t-tests, ANOVA, and chi-square tests for comparison between groups. Results: Data analysis was conducted on 90 patients with Type 2 Diabetes. The findings revealed a significant reduction in fasting blood sugar levels post-intervention in the Ma'aljobon Aftimouni group (134.27 ± 21.79 vs. 152.3 ± 31.37, mean difference 18.03 ± 5.63, 95 % CI: 6.53 to 29.53, p = 0.003). Additionally, a significant difference in HbA1c values was observed post-intervention in both the Ma'aljobon Aftimouni group (7.88 ± 0.77 vs. 8.09 ± 0.73, mean difference 0.21 ± 0.09, 95 % CI: 0.03 to 0.39, p = 0.031) and the Ma'aljobon without Aftimoun group (7.97 ± 0.84 vs. 8.25 ± 0.78, mean difference 0.28 ± 0.08, 95 % CI: 0.11 to 0.45, p = 0.002). Conclusion: The findings showed that daily consumption of Ma'aljobon supplements on an empty stomach before breakfast may have a beneficial effect on the glycemic indices of patients. However, further studies seem to be necessary in this regard.